Competitiveness and diversification of services exports in sub‐Saharan Africa. (25th December 2022) - Were, Maureen; Odongo, Maureen
Abstract: Trade in services has become the most dynamic segment of international trade. This paper examines the competitiveness of services exports in sub‐Saharan Africa (SSA) for the period 2005–2019 using revealed comparative advantage approach. The analysis shows that although SSA has a comparative advantage in traditional services, that is travel and transport, it has remained less competitive compared to other regions globally, and its share of world services exports is negligible. Moreover, SSA has not developed competitiveness in modern commercial services and, hence, continue to perform poorly. The results suggest only Nigeria and Kenya have so far developed comparative advantage in financial services. SSA's dismal performance of services exports can be attributed to various factors such as technological and infrastructure constraints, protectionist and regulatory barriers. There is need to rethink strategies of revamping and diversifying services esports to spur Africa's trade and economic transformation. These include leveraging the opportunities availed by the African Continental Free Trade Area (AfCFTA). Unexploited opportunities include Africa's rich cultural diversity, recreation, business and conferencing services.